The role of pain catastrophizing as a mediator in the work disability process following acute low back pain. Issue 1 (March 2017) - Besen, Elyssa; Gaines, Brittany; Linton, Steven J.; Shaw, William S.
Abstract : The purpose of this study was to assess pain catastrophizing as a mediator in the relationships between pain and recovery expectations with work limitations and functional disability in a working population experiencing acute low back pain (LBP). Workers ( n = 241) with acute, work‐related LBP completed measures of pain and injury at medical intake and then the Pain Catastrophizing Scale (PCS) shortly after the initial intake visit. At 3‐months follow‐up, measures of work limitations and functional disability were administered. Structural equation modeling was used to assess whether the PCS mediated longitudinal associations between pain and recovery expectations with perceived disability and work limitations. The PCS score completely mediated the relationship between initial pain intensity and 3‐month perceptions of disability (40% explained) and work limitations (29% explained). The PCS also completely mediated the longitudinal relationship between pain recovery expectations and 3‐month disability (50% explained) and work limitations (40% explained). Effective clinical management during this acute phase of LBP might be improved by incorporating early interventions to reduce catastrophizing in cases where pain catastrophizing may be especially problematic.